Adaptive Precision Control of Permanent Magnet Linear Motors - Huang, S.N.; Tan, K.K.; Lee, T.H. (Asian journal of control, 2002)
ABSTRACT This paper describes an adaptive control scheme developed for precision control of DC permanent magnet linear motors (PMLM). A sliding surface is defined on which a self‐tuning version of robust control capable of achieving tight set‐point regulation is developed, where the control gains are tuned using an adaptive algorithm. Parameter and states convergence properties of the adaptive controller are derived based on the control law formulated. Finally, simulation study and a real‐time experiment are provided to evaluate the performance of the proposed control system.